Penerapan pendidikan seksual dengan media visual storytelling pada anak usia dini ”Kujaga Diriku” - Rahmi, Dian; Rikayoni, Rikayoni (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Cases of sexual violence against children in Indonesia remain a serious problem and are increasing every year. One preventative measure that can be implemented is through the implementation of early sexual education delivered in a developmentally appropriate manner. Sexual education is crucial for helping children gain self-awareness from an early age and protecting them from various sexual crimes. To implement sex education for children, teachers need new innovations to develop children's knowledge of sex. One way to do this is through the use of learning materials and media. Purpose: To provide knowledge about sexual education for early childhood using visual storytelling as a promotional and preventive measure against child sexual violence. Method: This Community Service activity was conducted on October 7, 2025, at Lillah Kindergarten in Padang City. The study subjects included three teachers, five parents, and 50 children from groups A and B (aged 4–6 years). The material was delivered through a video presentation of